Forgiveness and love - Pettigrove, Glen. (Oxford : Oxford University Press, 2012)
What is forgiveness? When is it appropriate? Is it to be earned or can it be freely given? Is it a passion we cannot control, or something we choose to do? Glen Pettigrove explores the relationship between forgiving, understanding, and loving.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Forgiveness; Love